The impact of loneliness on healthcare use in older people: evidence from a nationally representative cohort - Ward, Mark (My University, 2020)
Aim: Concerns around loneliness leading to increased healthcare use persist in spite of a mixed evidence base and lack of adjustment for key potential confounders. We investigated the associations among loneliness, health and healthcare use in older adults including stratification to investigate whether these associations differ by gender. Subject and methods: Secondary analysis of a nationally representative sample of 8175 community-dwelling adults aged 50 years and over from The Irish Longitudinal Study on Ageing (TILDA). Primary outcomes were self-reported general practitioner (GP) and emergency department (ED) visits in the past 12 months. Negative binomial and logistic regression analysis was used to investigate associations between loneliness and healthcare use, later adjusting for potential mediators (health and health behaviours). Results: Loneliness was consistently positively associated with number of GP visits according to both cross-sectional and longitudinal analyses, with incidence rate ratios (IRRs) ranging from 1.08 to 1.33 in the sample overall. Associations with ED visits were less consistent. After adjusting for health and health behaviours, male loneliness does not appear to influence ED or GP visits. However, women who reported loneliness had an elevated risk of an ED visit at wave 1 (W1; odds ratio (OR) 1.08 [1.01–1.16]), as well as increased GP visits at both waves (IRRs ranging from 1.05 [1.02–1.07] to 1.16 [1.07–1.26]). Conclusion: Older women experiencing loneliness visit their GP more often irrespective of health, health behaviours or social isolation. While effect sizes were small, there are implications for health service resources at a population level. Importantly, however, this may also be a useful opportunity to redirect towards appropriate services and tailored resources.
PUBLISHED
Keywords: Loneliness, Healthcare use, Emergency department, General practitioner, Older adults, Primary care physician; Ageing